You are on page 1of 56

A-Level Maths:

Core 3
for Edexcel

C3.6 Differentiation

This icon indicates the slide contains activities created in Flash. These activities are not editable. For more detailed instructions, see the Getting Started presentation.
1 of 56 Boardworks Ltd 2006

The chain rule

The chain rule The relationship between

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

2 of 56

Boardworks Ltd 2006

Review of differentiation
So far, we have used differentiation to find the gradients of functions made up of a sum of multiples of powers of x. We found that:
If y = x n then dy = nx n 1 dx

and when xn is preceded by a constant multiplier k we have:

dy If y = kx then = knx n1 dx
n

Also:
dy If y = f ( x ) g( x ) then = f '( x ) g '( x ) dx
3 of 56 Boardworks Ltd 2006

Review of differentiation
We will now look at how to differentiate exponential, logarithmic and trigonometric functions. We will also look at techniques that can be used to differentiate: Compound functions of the form f(g(x)). For example:
x 1
2

3 x2

sin( x3 )

x ln x

xe 2 x

3 x 2 cos x

f ( x) Quotients of the form , such as: g( x ) 3 x +1 e2 x x2 1 sin x

4 of 56

x2 ln x
Boardworks Ltd 2006

The chain rule

The chain rule is used to differentiate composite functions. For instance, suppose we want to differentiate y = (2x + 1)3 with respect to x.
One way to do this is to expand (2x + 1)3 and differentiate it term by term. Using the binomial theorem:

(2 x +1)3 = 8 x3 + 3(4 x2 ) + 3(2 x) +1 = 8 x 3 +12 x 2 + 6 x +1 Differentiating with respect to x: dy = 24 x 2 + 24 x + 6 dx = 6(4 x2 + 4 x +1) = 6(2 x +1)2
5 of 56 Boardworks Ltd 2006

The chain rule

Another approach is to use the substitution u = 2x + 1 so that we can write y = (2x + 1)3 as y = u3. The chain rule states that:
If y is a function of u and u is a function of x, then dy dy du = dx du dx So if y = u3 dy = 3u 2 du where u = 2x + 1, du =2 dx

dy dy du Using the chain rule: = = 3u 2 2 dx du dx = 6u 2

= 6(2 x +1)2
6 of 56 Boardworks Ltd 2006

The chain rule

Use the chain rule to differentiate y = 3 x 2 5 with respect to x. Let

y =u

1 2

where

u = 3x2 5
du = 6x dx

1 dy 1 2 = 2u du

1 dy dy du 1 2 Using the chain rule, = = 2 u 6x dx du dx

= 3 xu

1 2
1 2

= 3 x(3 x 5)
2

=
7 of 56

3x 3 x2 5
Boardworks Ltd 2006

The chain rule

dy 2 Find given that y = . 3 4 dx (7 x ) 2 where u = 7 x3 Let y = 4 = 2u 4 u dy du = 8u 5 = 3 x 2 du dx dy dy du Using the chain rule: = = 8u 5 3 x 2 dx du dx
= 24 x 2u 5

= 24 x2 (7 x3 )5
24 x 2 = (7 x 3 )5
8 of 56 Boardworks Ltd 2006

The chain rule using function notation

With practice some of the steps in the chain rule can be done mentally. Suppose we have a composite function y = g(f(x)) If we let y = g(u) where u = f(x)

dy du = g '(u ) = f '( x ) then and du dx dy dy du Using the chain rule: = = g '(u ) f '( x) dx du dx

But u = f(x) so
dy = g '(f ( x )) f '( x ) If y = g(f(x)) then dx
9 of 56 Boardworks Ltd 2006

The chain rule

All of the composite functions we have looked at so far have been of the form y = (f(x))n.
In general, using the chain rule, If y = (f (x))n
dy = n( f ( x ))n 1 f '( x ) then dx

If we use to represent f (x) and write this rule more visually as:

to represent f (x) we can

y=

dy =n dy

n 1

Find the equation of the tangent to the curve y = (x4 3)3 at the point (1, 8).
10 of 56 Boardworks Ltd 2006

The chain rule

y= (x4 3)3
dy d 4 4 2 = 3( x 3) ( x 3) dx dx

= 3( x 4 3)2 4 x3 = 12 x3 ( x 4 3)2
When x = 1,
dy = 12(1 3)2 = 48 dx

Using y y1 = m(x x1) the equation of the tangent at the point (1, 8) is: y + 8 = 48(x 1) y = 48x 48 8 y = 48x 56 y = 8(6x 7)
11 of 56 Boardworks Ltd 2006

dx dy

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

12 of 56

dx dy

Suppose we are given x as a function of y instead of y as a function of x. For instance,

x = 4y2
dx We can find dy by differentiating with respect to y: dx = 8y dy

dy 1 dy dx = dx = 1, from which we get: dx dy dx dy dx So by the above result, if = 8y then dy dy 1 = dx 8 y

13 of 56 Boardworks Ltd 2006

dy The relationship between dx and

dx dy

Find the gradient of the curve with equation x = 2y3 3y 7 at the point (3, 2). x = 2y3 3y 7
dx = 6 y2 3 dy
At the point (3, 2), y = 2:

dx = 6(2)2 3 = 21 dy
dy 1 = dx We can now find the gradient using the fact that dx dy dy 1 = dx 21
14 of 56 Boardworks Ltd 2006

Differentiating inverse functions

dy 1 The result = dx is particularly useful for differentiating dx dy inverse functions. For example:
d (sin1 x ) writing your answer in terms of x. Find , dy
Let y = sin1 x so x = sin y

dx = cos y dy

Using the identity cos2y = 1 sin2y

1 dy 1 = = dx cos y 1 sin2 y
But sin y = x so
d 1 1 (sin x ) = dy 1 x2
15 of 56 Boardworks Ltd 2006

Differentiating ex and related functions

The chain rule The relationship between

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

16 of 56

Boardworks Ltd 2006

The derivative of ex
A special property of the exponential function ex is that
dy If y = e then = ex dx
x

From this, it follows that

If y = ke x then dy = ke x dx

where k is a constant. For example, if y = 4ex x3

dy = 4e x 3 x 2 dx
17 of 56 Boardworks Ltd 2006

Functions of the form ekx

Suppose we are asked to differentiate a function of the form ekx, where k is a constant. For example, Differentiate y = e5x with respect to x. Let
y = eu
dy = eu du

where

u = 5x
du =5 dx

In practice, we wouldnt need to include this much working.

18 of 56 Boardworks Ltd 2006

Functions of the form ekx

We would just remember that in general,
If y = e kx then dy = ke kx dx

For example,
d 7x ( e ) = 7e 7 x dx d 2 x (e ) = 2e 2 x dx

d e (e ) = dx 3 We can use the chain rule to extend this to any function of the form ef(x).
x 3
19 of 56

x 3

Functions of the form ef(x)

If y = ef(x) then we can let Let
then
y = eu
dy = eu du dy dy du = dx du dx

where

u = f(x)
du = f '( x ) dx

= eu f '( x) = f '( x )ef ( x )

So in general,

If y = e

f ( x)

dy then = f '( x )e f ( x ) dx

In words, to differentiate an expression of the form y = ef(x) we multiply it by the derivative of the exponent.
20 of 56 Boardworks Ltd 2006

Functions of the form ef(x)

Using to represent f(x) and
y=e

to represent f (x):
dy = dx e

For example,
dy 5 x 4 (e ) = 5e 5 x 4 dx dy 3 x e3 x (e ) = dx dy x2 9 x2 9 x2 9 (5e ) = 5 2 xe = 10 xe dx
21 of 56 Boardworks Ltd 2006

Differentiating ln x and related functions

The chain rule The relationship between

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

22 of 56

Boardworks Ltd 2006

The derivative of ln x
Remember, ln x is the inverse of ex.
So, if then y = ln x x = ey

Differentiating with respect to y gives: dx = ey dy dy 1 1 = dx = y dx dy e But ey = x so,

dy 1 = dx x dy 1 If y = ln x then = dx x
23 of 56 Boardworks Ltd 2006

Functions of the form ln kx

Suppose we want to differentiate a function of the form ln kx, where k is a constant. For example: Differentiate y = ln 3x with respect to x. Let

y = ln u
dy 1 = du u

where

u = 3x
du =3 dx

dy dy du 3 Using the chain rule: = = dx du dx u = 3 3x

1 = x
24 of 56 Boardworks Ltd 2006

Functions of the form ln kx

When functions of the form ln kx are differentiated, the ks will always cancel out, so in general,
dy 1 If y = ln kx then = dx x

We can use the chain rule to extend to functions of the more general form y = ln f(x). y = ln u Let where u = f(x) du dy 1 = = f '( x ) then du u dx
Using the chain rule:
dy dy du f '( x ) = = dx du dx u

f '( x ) = f ( x)
25 of 56 Boardworks Ltd 2006

Functions of the form ln (f(x))

In general, using the chain rule
dy f '( x ) If y = ln f ( x ) then = dx f ( x )
Using to represent f(x) and to represent f (x):

y = ln

dy = dy

For example,

d 7 ln(7 x 4) = 7x 4 dx d 9 x2 ln(3 x 3 + 8) = 3 dx 3x + 8

26 of 56

Functions of the form ln (f(x))

In some cases we can use the laws of logarithms to simplify a logarithmic function before differentiating it. Remember that, ln (ab) = ln a + ln b
a ln = ln a ln b b

ln an = n ln a

x Differentiate y = ln with respect to x. 2 x y = ln = ln x ln2 2

= ln x ln2
1 = 2 ln x ln2
27 of 56 Boardworks Ltd 2006

1 2

Functions of the form ln (f(x))

1 y = 2 ln x ln2

1 dy 1 1 = = dx 2 x 2x

ln 2 is a constant and so it disappears when we differentiate.

x If we had tried to differentiate y = ln without simplifying it 2 first, we would have had: 1 1 x 2 1 dy 4 1 x2 y = ln 2 = 1 dx 1 x 2
2

1
1 2 1 2

2x x 1 = 2x The derivative is the same, but the algebra is more difficult.

28 of 56 Boardworks Ltd 2006

The product rule

The chain rule The relationship between

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

29 of 56

The product rule

The product rule allows us to differentiate the product of two functions.
It states that if y = uv, where u and v are functions of x, then
dy dv du =u +v dx dx dx Find dy given that y = x 4 3 2 x . dx

Let So

u=

x4

and

v = (3 2 x )

1 2

du = 4 x3 dx

1 dv 1 2 = (3 2 x ) 2 dx 2

= (3 2 x )
30 of 56

1 2

The product rule

Using the product rule: 1 1 dy 2 4 3 2 = x (3 2 x ) + 4 x (3 2 x ) dx 1 1 4 3 2 2 x 4 x (3 2 x ) (3 2 x ) = 1 + 1 2 2 (3 2 x ) (3 2 x )

= = =

x 4 + 4 x3 (3 2 x ) (3 2 x ) (3 2 x ) 12 x3 9 x 4 (3 2 x )
1 2 1 2

x 4 +12 x3 8 x 4
1 2

3(4 x3 3 x 4 ) = 3 2x 31 of 56

The product rule

Give the coordinates of any stationary points on the curve y = x2e2x.
Let So u = x2 du = 2x dx and v = e2 x dv = 2e2 x dx

Using the product rule: dy = 2 x 2e2 x + 2 xe2 x dx = 2 xe2 x ( x +1) dy = 0 when 2 xe2 x = 0 or x +1= 0 dx 2 xe2 x = 0 x = 0 x +1= 0 x = 1
32 of 56 Boardworks Ltd 2006

The product rule

When x = 0, y = (0)2e0
=0

The point (0,0) is a stationary point on the curve y = x2e2x. When x = 1, y = (1)2e2
= e2 The point (1, e2) is also a stationary point on the curve y = x2e2x.

33 of 56

The quotient rule

The chain rule The relationship between

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

34 of 56

The quotient rule

The quotient rule allows us to differentiate the quotient of two functions. It states that if y = u , where u and v are functions of x, then v
dv dy v du u dx = dx 2 dx v

dy 2 x +1 Find given that y = . 2 dx 5x

Let So

u = 2x + 1
du =2 dx
35 of 56

and

v = 5x2
dv = 10 x dx
Boardworks Ltd 2006

The quotient rule

dy (5 x 2 )(2) (2 x +1)(10 x) = dx 25 x 4 10 x 2 20 x 2 10 x = 25 x 4
2x 4x 2 = 5 x3 2 x 2 = 5 x3 = 2( x +1) 5 x3

36 of 56

The quotient rule

Find the equation of the tangent to the ln x 4 at the point (1, 0). curve y = x2
u = ln x4 and v = x2 dv du 4 x3 1 = 2x = 4 = 4x So dx dx x Using the quotient rule: dy x 2 4 x 1 ln x 4 2 x = dx x4 Let
4 x 8 x ln x = x4 4(1 2ln x ) = x3
37 of 56

Using ln x4 = 4 ln x

The quotient rule

When x = 1, dy = 4(1 2 ln 1) dx 1 =4 The gradient of the tangent at the point (1, 0) is 4.
Use y y1 = m(x x1) to find the equation of the tangent at the point (1, 0). y 0 = 4(x 1) y = 4x 4
Remember that ln 1 = 0

38 of 56

Differentiating trigonometric functions

The chain rule The relationship between

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

39 of 56

40 of 56

The derivative of sin x

By plotting the gradient function of y = sin x, where x is measured in radians, we can deduce that
dy If y = sin x then = cos x dx

Functions of the form k sin f(x) can be differentiated using the chain rule.

Differentiate y = 2 sin 3x with respect to x.

So if y = 2 sin u
dy = 2cos u du
41 of 56

where

u = 3x
du =3 dx
Boardworks Ltd 2006

The derivative of sin f(x)

Using the chain rule:
dy dy du = 2cos u 3 = dx du dx = 6cos3x

In general using the chain rule,

dy If y = sin f ( x ) then = f '( x )cos f ( x) dx

Using

to represent f(x) and

to represent f (x):

y = sin

dy = dy

cos

42 of 56

43 of 56

The derivative of cos x

By plotting the gradient function of y = cos x, where x is measured in radians, we can deduce that
dy If y = cos x then = sin x dx dy Find given that y = x2 cos x. dx

Let So

u = x2
du = 2 x dx

and

v = cos x
dv = sin x dx

44 of 56

The derivative of cos x

Using the product rule: dy = x 2 ( sin x ) + cos x( 2 x ) dx = x 2 sin x 2 x cos x
= x( x sin x 2cos x )

Functions of the form k cos f(x) can be differentiated using the chain rule. Differentiate y = 3 cos (x3 4) with respect to x. So if y = 3 cos u
dy = 3 sin u du
45 of 56

where

u = x3 4
du = 3 x2 dx
Boardworks Ltd 2006

The derivative of cos x

Using the chain rule:
dy dy du = = 3 sin u 3 x 2 dx du dx = 9 x2 sin( x3 4)

In general using the chain rule,

dy If y = cos f ( x ) then = f '( x )sin f ( x) dx

Using

to represent f(x) and

to represent f (x):

y = cos

dy = dy

sin

46 of 56

The derivative of tan x

We can differentiate y = tan x (where x is in radians) by writing it as sin x y= cos x Then we apply the quotient rule with u = sin x and v = cos x :
dy cos x cos x sin x( sin x ) = dx cos2 x

= sec 2 x

dy If y = tan x then = sec 2 x dx

47 of 56 Boardworks Ltd 2006

The derivative of sec x

We can differentiate y = sec x (where x is in radians) by writing it as 1 y= = (cos x )1 cos x Then using the chain rule we get: dy = (cos x )2 ( sin x ) dx sin x = cos2 x 1 sin x = cos x cos x = sec x tan x
dy If y = sec x then = sec x tan x dx
48 of 56 Boardworks Ltd 2006

The derivative of cosec x

We can differentiate y = cosec x (where x is in radians) by writing it as 1 y= = (sin x )1 sin x
Then using the chain rule we get: dy = (sin x )2 (cos x ) dx cos x = 2 sin x 1 cos x = sin x sin x = cosec x cot x
dy If y = cosec x then = cosec x cot x dx
49 of 56 Boardworks Ltd 2006

The derivative of cot x

We can differentiate y = cot x (where x is in radians) by writing it as cos x y= sin x Then we apply the quotient rule with u = cos x and v = sin x:
dy sin x( sin x ) cos x cos x = dx sin2 x

= co sec 2 x

dy If y = cot x then = cosec 2 x dx

50 of 56 Boardworks Ltd 2006

Derivatives of trigonometric functions

In summary, if x is measured in radians, then
y = sin x dy = cos x dx y = sec x dy = sec x tan x dx

dy y = cosec x = cosec x cot x dx dy y = cot x = cosec 2 x dx

When learning these results, it is helpful to notice that all of the trigonometric functions starting with co have negative derivatives.
51 of 56 Boardworks Ltd 2006

Examination-style question
The chain rule The relationship between

Contents

dy dx

and

dx dy

Differentiating ex and related functions

Differentiating ln x and related functions The product rule

The quotient rule

Differentiating trigonometric functions Examination-style question

52 of 56

Boardworks Ltd 2006

Examination-style question
Given that f ( x ) =
2x , 2 x +4

a) find f (x), b) find the coordinates of any stationary points and determine their nature, c) sketch the curve y = f(x). a) Using the quotient rule: f '( x ) =
v du u dv dx dx v2

2( x 2 + 4) 2 x(2 x ) f '( x ) = ( x 2 + 4)2 2 x 2 + 8 4 x 2 2(4 x 2 ) = = 2 2 2 ( x + 4) ( x + 4)2

53 of 56 Boardworks Ltd 2006

Examination-style question
2(4 x 2 ) =0 b) When f(x) = 0, 2 2 ( x + 4)

2(4 x2 ) = 0
4 x2 = 0

x = 2
When x = 2, y =
4 1 = 8 2

4 1 When x = 2, y = = 8 2 2x f( x ) = 2 Therefore, the graph of the function has turning x +4 1 1 points at (2, 2 ) and (2, 2).
54 of 56 Boardworks Ltd 2006

Examination-style question
Looking at the gradient just before and just after x = 2:
x dy 2(4 x 2 ) = 2 Value of dx ( x + 4)2 Slope 1.9 0.01
+ive

2 0
0

2.1 0.01
ive

Looking at the gradient just before and just after x = 2:

x dy 2(4 x 2 ) = 2 Value of dx ( x + 4)2 Slope 2.1 0.01
ive

2 0
0

1.9 0.01
+ive

1 So (2, 2 ) is a minimum point.

55 of 56 Boardworks Ltd 2006

Examination-style question
2x c) The curve y = 2 crosses the axes when x = 0 and when x +4 y = 0.

When x = 0, y = 0.

(Also, when y = 0, x = 0).

Therefore the curve has one crossing point at the origin, a 1 1 minimum at (2, 2 ) and a maximum at (2, 2 ):
y
1 2

Also,
y=
2

2x x2 + 4
x

as x , y 0

0
1 2

and,
as x , y 0+.

56 of 56